2011
DOI: 10.1186/1748-7161-6-14
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of low grade isthmic spondylolisthesis; a randomized controlled study of the surgical fixation with and without reduction

Abstract: Backgroundspondylolisthesis is a condition in which a vertebra slips out of the proper position onto the bone below it as a result of pars interarticularis defect. The slipped segment produces abnormal positioning of the vertebrae in relation to each other along the spinal column and causes mechanical back pain and neural breach.Materials and methodsA randomized and double blinded study consisted of 41 patients aged 36-69 years (18 females and 28 males) treated for symptomatic spondylolisthesis between Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…Although slip reduction can provide better function of the lumbosacral junction, at least in theory, several authors have recommended in situ fusion surgery rather than reduction surgery, considering postoperative complications such as neurological deficits. 1,[4][5][6]11,13,17,20,26,27,29 On the other hand, previous reports have detailed that pseudarthrosis rates were decreased by reduction. 2,3,12,19,28,30,31,33 Therefore, surgery for isthmic spondylolisthesis requires management of both postoperative neurological deficits and the union rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although slip reduction can provide better function of the lumbosacral junction, at least in theory, several authors have recommended in situ fusion surgery rather than reduction surgery, considering postoperative complications such as neurological deficits. 1,[4][5][6]11,13,17,20,26,27,29 On the other hand, previous reports have detailed that pseudarthrosis rates were decreased by reduction. 2,3,12,19,28,30,31,33 Therefore, surgery for isthmic spondylolisthesis requires management of both postoperative neurological deficits and the union rate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to decompression, reduction of the slipped vertebrae as a part of surgical approach is still a controversial issue in spine surgery [20, 21] . In a randomized and double blinded study of symptomatic patients with Meyerding grade I and II isthmic spondylolisthesis, Audat et al concluded that the outcome is almost similar in patients who underwent surgical fixation and decompression with or without reduction of the slippage [20] . Many other authors proposed that reduction of the slippage should be considered to correct sagittal deformity and enhance the spinal biomechanics [22, 23] .…”
Section: Discussionmentioning
confidence: 99%
“…However, it still remains controversial whether to reduce the spondylolisthesis or to fuse in situ (4,23,24,36,46). The present study compared the complications, perioperative factors, and fusion success in patients undergoing MI-TLIF for degenerative spondylolisthesis between those in whom reduction occurred and in those that were fused in situ.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have investigated MI-TLIF for multiple spinal pathologies; however, few have specifically investigated MI-TLIF in degenerative spondylolisthesis, and to our knowledge, none have compared the perioperative outcomes for reduction or fusion in situ. In contrast, a few studies have investigated this in patients undergoing other methods of arthrodesis (4,8,23,24,29,36). Thus far, the literature supports the notion that reduction does not increase the risk of complications, most importantly neurological deficit, and the clinical and radiographic outcomes are similar with the exception of possible improved fusion rates when reduction is employed (24).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation